The Fuegian thrust-fold belt: From arc-continent collision to thrust-related deformation in the southernmost Andes - Torres Carbonell, Pablo Juan; Cao, Sebastián José; Gonzalez Guillot, Mauricio Alberto; Mosqueira González, María Victoria; Dimieri, Luis Vicente; Duval, Florian; Scaillet, Stéphane (Journal of South American Earth Sciences)
New detailed structural data from the Fuegian Andes including new ages and cross-cutting relationships with intrusive rocks, as well as an appraisal of published structural data, support that this orogen evolved as a basement-involved thrust-fold belt after initial formation in an arc-continent collision scenario. New structural data from a deformed 84 Ma intrusive indicate that structures from the collisional event in the Argentine Fuegian Andes are of Campanian age, comprising only the youngest and less intense deformation of the orogenic wedge. In the internal thrust-fold belt, these structures are cut by intrusives with new ages of 74 Ma (Ar/Ar on hornblende). The superposition of thrusts on these early structures indicates a subsequent event in which a thrust-fold belt formed since the Maastrichtian-Danian. Additional new data confirm brittle-ductile thrusting in the central belt, with thrusts joining a common upper detachment in the base of the Lower Cretaceous rocks. These thrusts formed a first-order duplex system that transferred the shortening accommodated in the foreland until the Miocene. Fil: Torres Carbonell, Pablo Juan. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Cao, Sebastián José. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego, Antártida e Islas del Atlántico Sur. Instituto de Ciencias Polares, Ambientales y Recursos Naturales; Argentina Fil: Gonzalez Guillot, Mauricio Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego, Antártida e Islas del Atlántico Sur. Instituto de Ciencias Polares, Ambientales y Recursos Naturales; Argentina Fil: Mosqueira González, María Victoria. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina ...